2016
DOI: 10.1177/0954409716657848
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of eddy current inspection in railway rail evaluation

Abstract: At the moment, one of the most cost-effective ways to inspect a whole railway network for rolling-contact fatigue is to carry out an eddy current inspection. It has a great sensitivity to even the smallest near surface defects, but this can also be a downside as it can lead to indications of deep damage from an array of tiny cracks. This can lead to overestimation of damage severity. Moreover, sizing of cracks in rails is unreliable due to the large number of parameters that affect the eddy current inspection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The limitations of EC inspection of rails are analyzed in Ref. [24]. Some of the most recent advances in EC-based testing of rails are illustrated in Refs.…”
Section: Ec-based Methodsmentioning
confidence: 99%
“…The limitations of EC inspection of rails are analyzed in Ref. [24]. Some of the most recent advances in EC-based testing of rails are illustrated in Refs.…”
Section: Ec-based Methodsmentioning
confidence: 99%
“…118 This technology is sensitive to lift-off distances (no more than 2 mm away) and is only valid for surface defects detection. 119 A typical speed of 75 km/h has been achieved in the developed vehicle as shown in Figure 7. 120124…”
Section: Short-range Rail Ndt Technologiesmentioning
confidence: 99%
“…Potential risk areas, in which defects may be hidden from the ultrasonic measurements, can then be identified. Furthermore, Rajamäki et al [20] suggest that eddy-current measurements should be complemented by visual inspection methods. For that purpose, the proposed method could be used as a high-fidelity visual inspection system.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Eddy-current testing complements the ultrasonic testing as it can detect surface defects. Rajamäki et al [20] found a penetration depth of 3 mm to be the practical limit. However, the resolution decays exponentially with depth.…”
Section: Introductionmentioning
confidence: 99%